Penal Sanctions for Psychological Domestic Violence under Utilitarianism Theory: A New Sentencing Paradigm in the 2023 Indonesian Criminal Code - Nasyi'ah, Iffaty; Saifullah, Saifullah; Hidayah, Khoirul; Roibin, Roibin; Adityo, Rayno Dwi (El-Usrah: Jurnal Hukum Keluarga, 2025)
Article 45 of the Law on the Elimination of Domestic Violence (UU PKDRT) regulates the penal sanctions for the criminal act of psychological violence, stipulating a maximum imprisonment of four months for minor offenses and up to three years for serious offenses. However, custodial sentences are deemed less effective, as they do not fully provide benefits to the parties involved, namely the victim, the perpetrator, the household, and society at large. Meanwhile, the 2023 Indonesian Criminal Code (KUHP 2023) introduces a new paradigm of sentencing that emphasizes restorative and rehabilitative justice, shifting from a solely punitive orientation to one that also considers victim recovery and offender rehabilitation. This study aims to analyze the implementation of the sentencing system under KUHP 2023 through the lens of Jeremy Bentham’s utilitarianism theory. The research employs a normative juridical method, utilizing statutory, conceptual, and case-based approaches. Primary legal materials include the UU PKDRT and KUHP 2023, while the conceptual framework is grounded in Bentham's utilitarianism. As tertiary support, interviews were conducted with three judges from the court of first instance. The findings indicate that alternative sanctions such as rehabilitation, probation, or community service are more effective in preventing recidivism and promoting social balance. The role of judges is pivotal in applying more proportionate sentencing, including through the mechanism of rechterlijk pardon (judicial pardon) in certain cases that meet legal and humanitarian considerations. Through this approach, the new sentencing system is expected to be more justice-oriented, to provide better protection for victims, and to serve as a more effective means of preventing psychological violence in domestic settings